A new genus of armored catfish (Siluriformes: Loricariidae) from the Greater Amazon, with a review of the species and description of five new species - Reis,Roberto E. (2022)
Abstract A new genus of Hypopopomatinae armored catfish is described from the northern portions of South America, namely the Amazon, Orinoco and Guianan coastal drainages. The new genus is diagnosed from all remaining hypoptopomatines by having the canal cheek plate on the ventral surface of the head posteriorly elongated and contacting the cleithrum, in addition to other features that distinguish the new genus from specific genera. Five new species are described and 18 species currently allocated in Parotocinclus, Hisonotus, and Curculionichthys are transferred to the new genus and rediagnosed. Parotocinclus amazonensis and P. aripuanensis are considered junior synonyms of P. britskii. The secondary sexual dimorphism of the members of the new genus is detailed and illustrated. Morphological characters are used to delimit four phenotypic groups of species that might have phylogenetic significance, which still have to be properly tested. A key to the species is offered and diagnoses, illustrations, and distribution maps are provided for all species.